A model of progressive photo-oxidative degeneration and inflammation in the pigmented C57BL/6J mouse retina. (June 2016) - Natoli, Riccardo; Jiao, Haihan; Barnett, Nigel L.; Fernando, Nilisha; Valter, Krisztina; Provis, Jan M.; Rutar, Matt
Abstract: Light–induced degeneration in rodent retinas is an established model for of retinal degeneration, including the roles of oxidative stress and neuroinflammatory activity. In these models, photoreceptor death is elicited via photo-oxidative stress, and is exacerbated by recruitment of subretinal macrophages and activation of immune pathways including complement propagation. Existing light damage models have relied heavily on albino rodents, and mostly using acute light stimuli. These albino models have proven valuable in uncovering the pathogenic mechanisms of such pathways in the context of retinal disease. However, their inherent albinism hinders comparability to normal retinal physiology, and also makes gene technology analysis time-consuming due to the predominance of the pigmented mouse strains in these applications. In this study, we characterise a new light damage model utilising C57BL/6J mice over a 7 day period of chronic light exposure. We use high-efficiency LED technology to deliver a sustained intensity of 100 k lux with negligible modulation of ambient temperature. We show that in the C57BL/6J mouse, chronic light exposure elicits the cardinal features of light damage including photoreceptor degeneration, atrophy of the choriocapillaris, decreased retinal function and increases in oxidative stress markers 4-HNE and 8-OHG, which emerge progressively over the 7 day period of exposure. These changes are accompanied by robust recruitment of IBA1+ and F4/80 + microglia/macrophages to the ONL and subretinal space, followed the strong up-regulation of monocyte-chemoattractants Ccl2, Ccl3, and Ccl12, as well as increases in expression of complement component C3 . These findings are in agreement with prior damage models conducted in albino rodents such as Balb/c mice, and support the use of this new model in further investigating the causative features of oxidative stress and inflammation in retinal disease. Highlights: Novel light damage model using LED technology on pigmented C57BL mice. Chronic retinal degeneration causing recruitment of macrophages. Photoreceptor cell death caused altered inflammatory and oxidative damage markers. Decrease in retinal functional changes in new light damage model. New model enables the discovery of mechanisms that underpin retinal disease.